El quantificador focal «pla»: un estudi de sintaxi dialectal - Rigau, Gemma (Caplletra. Revista Internacional de Filologia, 2004)
This article offers a microsyntactic study on a dialectal topic. Its aim is to describe the syntactic, semantic and intonational behavior of sentences containing the adverb «pla». This adverb, which belongs to some North-Eastern Catalan dialects, has a focalizing role. In this paper it is argued that its focalizing value derives from its epistemic modal meaning. The case in which the presence of «pla» gives a negative meaning to the sentence is especially interesting. The paper shows that in this case an abstract negative polarity operator has to be posited.